2022
DOI: 10.33043/sswj.1.1.163-182
|View full text |Cite
|
Sign up to set email alerts
|

Collegiate Athletes Engaging in Activism: Perceptions of Social Justice Causes and Support from Significant Social Agents

Abstract: Recently, collegiate athletes have used their platform to promote positive social change. Some possibilities for the increase of activism is athletes’ perceptions of societal issues and support from key social agents. However, these perceptions have been largely unexplored. The current study aimed to address those gaps by investigating collegiate athletes’ perceptions and investigating if various demographic characteristics influence the likelihood of activism engagement. Participants (n = 4,473) completed sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
3
10
0
Order By: Relevance
“…Research has found that social support from coaches, teammates, friends, family, and sport administrators are beneficial for college athlete mental health and well-being and decreases burnout (Cho et al, 2020; DeFreese & Smith, 2013, 2014; Gabana et al, 2017; Hagiwara et al, 2017) and social support from teammates, coaches, and athletic trainers has related to improved recovery, well-being, satisfaction, and resilience (e.g., Corbillon et al, 2008; Galli & Vealey, 2008; Judge et al, 2012; Lu & Hsu, 2013). Emerging research on support for athlete activism, while limited, has found that perception of support is an important aspect of athletes’ experience engaging in activism (Martin et al, 2022). For example, Martin et al (2022) found that athletes engaging in activism generally felt supported by parents, friends, and teammates, which “speaks to the importance of support from nonathletic department sources, even for collegiate athletes, and supports the idea that these individuals might be the most influential when athletes are deciding on whether or not to engage in activism” (p. 175).…”
Section: Challenges For Athlete Activistsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has found that social support from coaches, teammates, friends, family, and sport administrators are beneficial for college athlete mental health and well-being and decreases burnout (Cho et al, 2020; DeFreese & Smith, 2013, 2014; Gabana et al, 2017; Hagiwara et al, 2017) and social support from teammates, coaches, and athletic trainers has related to improved recovery, well-being, satisfaction, and resilience (e.g., Corbillon et al, 2008; Galli & Vealey, 2008; Judge et al, 2012; Lu & Hsu, 2013). Emerging research on support for athlete activism, while limited, has found that perception of support is an important aspect of athletes’ experience engaging in activism (Martin et al, 2022). For example, Martin et al (2022) found that athletes engaging in activism generally felt supported by parents, friends, and teammates, which “speaks to the importance of support from nonathletic department sources, even for collegiate athletes, and supports the idea that these individuals might be the most influential when athletes are deciding on whether or not to engage in activism” (p. 175).…”
Section: Challenges For Athlete Activistsmentioning
confidence: 99%
“…Emerging research on support for athlete activism, while limited, has found that perception of support is an important aspect of athletes’ experience engaging in activism (Martin et al, 2022). For example, Martin et al (2022) found that athletes engaging in activism generally felt supported by parents, friends, and teammates, which “speaks to the importance of support from nonathletic department sources, even for collegiate athletes, and supports the idea that these individuals might be the most influential when athletes are deciding on whether or not to engage in activism” (p. 175).…”
Section: Challenges For Athlete Activistsmentioning
confidence: 99%
“…College Soccer Players' Perceptions of and Need for Soccer Agents Sports agents are professionals who perform negotiations for scouting or annual salary contracts with professional sports teams on behalf of the athletes they represent and carry out activities to enhance their economic values through efficient management of their sports activities (Martin et al, 2022). In the in-depth interviews conducted in this study, 10 out of 14 college soccer players showed a positive attitude toward the services of sports agents such as signing opportunities, player management, player value enhancement, data management, and supply support, while four showed a negative attitude due to inappropriate and fraudulent agent activities and high fees.…”
Section: Resultsmentioning
confidence: 99%
“…At the macro-level, findings from the current study highlight sport social workers' commitment to social justice, which helps to advance the understanding of sport social workers from a non-clinical perspective. As sport is a microcosm of society (Newman et al, 2019), athletes have continued to speak out against systemic inequities and economic, political, and social injustices (Kluch, 2021;Mac Intosh et al, 2020;Martin et al, 2022). Thus, sport social workers-due to the NASW Code of Ethics-may be uniquely educated and trained to disrupt injustice and promote social change.…”
Section: Discussionmentioning
confidence: 99%